SETTLEMENT OF FACE RECOGNITION OF HIS GUILT IN THE CRIME IN SOME FOREIGN JURISDICTIONS - Akhmetova Диана Канатовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In the article an author examines the features of settlement in some foreign legislation questions of institute of confession of the guilt in the commission of crime. Study and comparison of norms of legislation of foreign countries, fastening the order of receipt and law consequences of confession the face of the guilt in the commission of crime, allows to draw conclusion about possibilities of their use in Kazakhstan criminal procedure.